Performa Pertumbuhan dan Kelangsungan Hidup Kepiting Bakau (Scylla serrata) dengan Pemberian Kombinasi Pakan Keong Mas dan Ikan Rucah - Lo Ode Muhammad Harisud; Endang Bidayani; Ahmad Fahrul Syarif (Universitas Bangka Belitung, 2019)
Mud crab (Scylla serrata) is the one of the commodities that have high economic value and potential to be cultivated. This research aimed to evaluate the growth performance of mud crab feeding with combinations of golden snail and trash fishes. The test material used was mud crab with an average weight of 111.16 grams as number of 36 individuals. The method used in this research was experimental method using a Completely Randomized Design (CRD). The treatment was golden snail as a feed, a combination of golden snail and trash fishes and trash fishes as feed. The results showed that combination feeding did not significantly affect of the growth and survival of mud crabs. The absolute weight in the treatment of golden snail feed was 24.30 ± 4.69 grams, the combination of golden snail and trash fishes was 19.34 ± 4.54 grams and the treatment of trash fishes as feed was 26.03 ± 8.11 grams. The absolute length of the treatment of golden snail feeding was 0.26 ± 0.08 cm, the combination of golden snail and trash fishes was 0.24 ± 0.05 cm and the treatment of trash fishes as feed was 0.36 ± 0.11 cm. The avrages percentage of survival for each treatment was 83.33%.